Rh-Decorated Three-Dimensional Graphene Aerogel Networks as Highly-Efficient Electrocatalysts for Direct Methanol Fuel Cells - Yang, Ying; Song, Yuexin; Sun, Hao; Xiang, Danyang; Jiang, Quanguo; Lu, Zhiyong; He, Haiyan; Huang, Huajie (Frontiers in Energy Research, 2020)
The exploration and development of highly-efficient Pt-alternative catalysts with acceptable costs are very essential for the large-scale commercial applications of direct methanol fuel cell (DMFC) technology. Herein, we demonstrate a facile and cost-effective self-assembly approach to the bottom-up fabrication of Rh-decorated three-dimensional graphene aerogel (Rh/3D-GA) networks as efficient DMFC anode catalysts. With the distinct textural features including large surface area, 3D porous structure, uniform Rh dispersion, and good electron conductivity, the resultant Rh/3D-GA hybrid architecture shows superior electrocatalytic properties toward methanol oxidation reaction, such as large electrochemically active surface area, low onset potential, high mass activity as well as excellent long-term stability, all of which are more competitive than those of Rh catalysts deposited on conventional carbon black, carbon nanotubes, and two-dimensional graphene supports.